2021
DOI: 10.3390/jcm10061296
|View full text |Cite
|
Sign up to set email alerts
|

Hypoperfusion Index Ratio as a Surrogate of Collateral Scoring on CT Angiogram in Large Vessel Stroke

Abstract: Background: This study was to evaluate the correlation of the hypoperfusion intensity ratio (HIR) with the collateral score from multiphase computed tomography angiography (mCTA) among patients with large vessel stroke. Method: From February 2019 to May 2020, we retrospectively reviewed the patients with large vessel strokes (intracranial carotid artery or proximal middle cerebral artery occlusion). HIR was defined as a Tmax > 10 s lesion volume divided by a Tmax > 6 s lesion volume, which was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
(50 reference statements)
2
8
0
Order By: Relevance
“…Thus, HIR has an impact on the evolution of the ischemic lesion. Our results correspond to previous studies, which could show that lower HIR is associated with a smaller infarct growth and better collateral circulation [ 17 , 18 , 21 , 22 , 23 ]. In the group of favorable HIR, FIV was rather overestimated by the perfusion software solutions with the exception of Brainomix, while it was generally underestimated in the group of unfavorable HIR.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, HIR has an impact on the evolution of the ischemic lesion. Our results correspond to previous studies, which could show that lower HIR is associated with a smaller infarct growth and better collateral circulation [ 17 , 18 , 21 , 22 , 23 ]. In the group of favorable HIR, FIV was rather overestimated by the perfusion software solutions with the exception of Brainomix, while it was generally underestimated in the group of unfavorable HIR.…”
Section: Discussionsupporting
confidence: 92%
“…Analogously, we found that ASPECTS at baseline and on follow-up imaging and the risk of developing malignant edema were significantly associated with the HIR. The median HIR in our study lies within the range of the cutoff values applied in previous studies (0.4–0.7) [ 17 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, further research is necessary to define a generally valid cutoff value for HIR.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…21 Our analysis supports the hypothesis and explores perfusion imaging parameters to potentially guide anesthesia choice. Although HIR may have shown good correlation with collaterals flow on CT angiogram, 15,22,23 variations within good and poor grades of HIR may have contributed to some of our findings.…”
Section: Discussionmentioning
confidence: 67%
“…In patients suffering from AIS, collateral circulation plays an important role in maintaining the blood flow to the tissue at risk of becoming ischemic, and in reducing the risk of hemorrhagic transformation in patients undergoing MT [ 14 ]. HI has been shown to be a good surrogate for predicting the CS in patients with acute LVO [ 15 ]. Various previous studies have explored the association between patient baseline characteristics and the CS, however variable results have been reported, most likely due to the heterogenous nature of the patient population [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%